Why Imre Lakatos’ Epistemological Method Best Suits Research in Urbanization: The Case of The Muslim Built Environments - Akbar, Jamel (Emerald, 2025)
Purpose This study explores why Lakatos’ epistemological framework is optimal for urbanization research, using Muslim built environments to demonstrate how rights-based approaches (Ḥuqūq) offer alternative methodologies. Design/methodology/approach Employing Lakatos’ methodology of scientific research programs (MSRP), the study treats Ḥuqūq as the “hard core” and comparatively analyses Popper’s falsificationism, Kuhn’s paradigm theory and Lakatos’ MSRP through case studies of Muslim urban environments. Findings Western paradigms often reduce Islamic environments to morphology, neglecting rights mechanisms. Ḥuqūq fosters self-regulation, preventing harm and ensuring equity. Lakatos’ framework better accommodates urban dynamism. Research limitations/implications Focused on theoretical analysis, the study calls for empirical validation. Future research could examine contemporary Ḥuqūq-based urban developments, repositioning rights as foundational in urban theory. Practical implications The study proposes a community-centric urban model, advocating local decision-making to address pollution and inequality. Insights are relevant for participatory governance and sustainable development. Originality/value Using Lakatosian epistemology with Islamic urbanism, this study advances cross-cultural urban theory by presenting alternative frameworks to dominant Western models.
Keywords: Research Method; Epistemology; Lakatos; Rights; Built Environment; Islamic Urbanism